Noninvasive programmed stimulation in the setting of ventricular tachycardia catheter ablation. (30th April 2020) - Frontera, Antonio; Prolic Kalinsek, Tine; Hadjis, Alexios; Della Bella, Paolo
Abstract: In the setting of catheter ablation of ventricular tachycardia (VT), invasive programmed ventricular stimulation (PVS) is considered an important tool to assess the (residual) inducibility of ventricular arrhythmias and determine the acute success of the procedure. In patients with cardiovascular implantable electronic devices, noninvasive programmed stimulation via implantable cardioverter‐defibrillator (ICD) leads can be an alternative to the invasive PVS with intracardiac catheters. The advantages of noninvasive programmed stimulation include preprocedure planning of the electrophysiology procedure to ensure optimal conditions for successful catheter ablation of VT. Following the procedure, noninvasive programmed stimulation has been shown to be used as a guide for repeat early ablation, to offer better programming of ICD, to offer prognostic value regarding the VT recurrence, and to guide antiarrhythmic drug therapy. The noninvasive nature of noninvasive programmed stimulation makes it an attractive alternative to PVS in patients with ICD who have not undergone catheter ablation of VT to obtain prognostic value regarding the occurrence of VT.